Reportazh o press-konferentsii . Reportazh o press-konferentsii . Report on a Press Conference . Репортаж о пресс-конференции - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Conference attended by Soviet and foreign journalists on Ukrainian and Polish nationalists' subversive activities. Featured in the program: Chornii, Vladimir Lazarevich (Head of the Ministry of Foreign Affairs) Contributors: Ukrainskoe televidenie (Studio) Конференция с участием советских и иностранных журналистов по поводу подрывной деятельности националистов в Украине и Польше. В программе участвуют: Чорний, Владимир Лазаревич (Руководитель министерства иностранных дел) Создатели: Украинское телевидение (Студия)